2023
DOI: 10.1111/1556-4029.15305
|View full text |Cite
|
Sign up to set email alerts
|

Collecting touch DNA from glass surfaces using different sampling solutions and volumes: Immediate and storage effects on genetic STR analysis

Janine Schulte,
Nicole Rittiner,
Ilona Seiberle
et al.

Abstract: Touch DNA has become increasingly important evidence in todays' forensic casework. However, due to its invisible nature and typically minute amounts of DNA, the collection of biological material from touched objects remains a particular challenge that underscores the importance of the best collection methods for maximum recovery efficiency. So far, swabs moistened with water are often utilized in forensic crime scene investigations for touch DNA sampling, even though an aqueous solution provokes osmosis, endan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…With respect to subsequent downstream analysis, it is essential to note that a low quantification result does not necessarily result in a profiling failure using standard forensic amplification kits, which, however, remains to be investigated for further in-depth downstream genetic analyses. For example, research demonstrated that DNA profiles could be generated from samples with literally no DNA quantities [ 39 , 50 ]. Moreover, the alleged imprints of the medical records before 1940 posed a challenge in differentiation from the paper discoloration that occurs with the age of the patient’s files and/or medical illustrations that inherently lack DNA content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to subsequent downstream analysis, it is essential to note that a low quantification result does not necessarily result in a profiling failure using standard forensic amplification kits, which, however, remains to be investigated for further in-depth downstream genetic analyses. For example, research demonstrated that DNA profiles could be generated from samples with literally no DNA quantities [ 39 , 50 ]. Moreover, the alleged imprints of the medical records before 1940 posed a challenge in differentiation from the paper discoloration that occurs with the age of the patient’s files and/or medical illustrations that inherently lack DNA content.…”
Section: Discussionmentioning
confidence: 99%
“…From a forensic standpoint, it remains controversial whether the majority of the detected DNA quantities are appropriate for additional analyses, including classical short tandem repeat (STR) analysis utilizing multiplex polymerase chain reaction (PCR) or using single nucleotide polymorphisms (SNPs) and next-generation sequencing (NGS) [ 70 72 ]. Recent advances in the sensitivity of techniques and reagents have enabled DNA profiling from quantities as low as contact traces [ 50 , 73 ] or even individual cells [ 74 ]. Further, NGS has successfully analyzed degraded samples from human remains and artificially degraded DNA through UV treatment [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schulte et al concluded that the prewetting volume has no significant effect on DNA yield and that 70% ethanol and 0.10% v/v Triton X-100 are both suitable as moistening solutions for the collection of touch DNA. Also, SDS can be used but tends to foam when higher concentrations are used, and Triton X-100 is extremely viscous, which makes its handling more difficult [27]. Canfield et al recommend the use of AutoMACS running buffer (containing BSA, EDTA, and azide) for the recovery of intact leukocytes over PBS or water in combination with nylon-flocked swabs (instead of cotton or dissolvable swabs) [28].…”
Section: Buffer Solutionmentioning
confidence: 99%